Determinants of audit quality during the Covid-19 pandemic - Puspaningsih, Abriyani; Larasati, Irena Safira (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2024)
This study aims to determine the effect of audit risk, time budget pressure, auditor motivation, audit complexity, and professional skepticism on audit quality during the COVID-19 pandemic. The study population was public accountants who worked at public accounting firms and had performed auditing. A purposive sampling technique was used to select a sample of 55 participants. Data were collected using a questionnaire that had been tested for validity and reliability. Multiple regression was used to analyze the data. The results of this study indicated that audit risk, time budget pressure, and audit complexity had negative effects on audit quality. Meanwhile, auditor motivation and professional skepticism were shown to have positive effects on audit quality. The findings of this research suggest that audit risk, time budget pressure, and audit complexity should be minimized to maximize audit quality. Meanwhile, auditor motivation and professional skepticism should be maximized to achieve audit quality.